(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
In terms of theory, practise, and perceptions of new methodologies and methods in feminist narrative practise, as well as their subversions in psychosexual and social constructions, have been used to contrast the plight of Indian women in society with how they are portrayed in literature. In the context of contact linguistics, the research paper examines Indian women's predicament in South Asian culture with regard to the problem of migration and its effects on diasporic communities. It also intends to investigate how these women are portrayed in literature in theory and in practise, truth and fiction, reality and myth. The analysis results in women authors' assessments of new methodologies and techniques in feminist narrative practise as well as their subversions of their resolves to the methods of writing beyond the conventional ending that critically assess and resolve essential concerns. Should the women voluntarily relinquish and compromise their own aspirations in preference of engagement or marriage? Or is it really a feminine subversion tactic used to subvert the existing dominating norm? Do they anticipate alternative female techniques, protest against alliances or marriages in psychosexual and societal constructions, or otherwise oppose them in their female-centered fiction? Does that provide opposing or alternative definitions of femininity in the context of Indian culture? Do they really support the feminist movement? Do these inclinations lead to a feminist interpretation of ‘separatist feminism', 'a radical protest against marriage', or as a detached fashionable posture, a concern with women rather than a positive culture-sensitive process of societal transformation and personal growth? Does it succeed in assisting them realise their objectives for independence, self-expression, self-fulfilment, and self-actualization? The weight of the feminine experience is the road to self-hood and independence, which eventually "becomes a cultural motif" in society. The resolution and resurrection are ultimately attained in and through society and literature.